COMMUNITY ENERGY MANAGEMENT FOR ENERGY SECURITY: THE PROJECT FOR ENERGY PLANNING IN 80 COMMUNITIES IN RESPONSE TO “SUFFICIENCY ECONOMY” AS INITIATED BY HIS MAJESTY THE KING - บุญญานุสาสน์, วีรวุฒิ; ภัทรนรากุล, ไพโรจน์; ณ ระนอง, อัญชนา (Sripatum Review of Humanities and Social Sciences, 2018)
This research aims to study community energy management for energy security, especially to study the household production and uses of biomass energy including the outputs, and outcomes. It employed the qualitative research methodology to study 12 communities. Research data were obtained by interviews, observations, and examination of secondary source data in terms of documents and evidences. The research findings show that there are six key success factors in community energy management, namely, the natural capital, financial/economic capital, human capital, social capital, community organizations and other related organizations, and biomass energy and other related energy technologies. The household production and uses of biomass energy must be promoted via the formulation of energy planning, the building of community capacity on energy, the transfer of local wisdom on energy, the utilization of community capital and resources, and the development of energy coordination networks both within and outside of the community. The outputs are the produced biomass energy fuels and the household uses of biomass energy. The success outcomes are the community economy improvement in terms of greater energy security, the social and environment improvement of the community, and the community’s self-reliance on energy. KEYWORDS: community energy management, biomass energy